Analisis Pengaruh Lingkungan Kerja Non Fisik Dan Kompensasi Terhadap Tingkat Kinerja Karyawan Pt. Telkom Indonesia Witel Solo, Tbk - Hekmah Citra Dewi, Arista, Dra.Chuzaimah, MM (2017)
Employee performance is a result of working an employee in the line of duty in accordance with the responsibility of that are imposed on all employees .The purpose of this study is to find the influence of work environment non-physical and compensation on the performance of an employee of PT.Telkom indonesia witel solo , tbk . Partial evaluation and simultaneous .The kind of research this is quantitative research , all employees of the population which totaled 176 an employee with 85 sample as respondents .The sample collection using a technique simple random sampling slovin with the formula .While data collection techniques research through the questionnaire covered with a scale likert and questionnaires open . Based on the calculation on with using program spss 16.0 the results of the analysis test t known that the variable work environment non-physical do not have effect on employee performance because the results of 0,730 & lt; 1,989 so ho received and ha rejected .While on the variables of compensation impact on of employee performance because the results of 3,248 & gt; 1,989 so ho were rejected and ho accepted .Seen from the test f obtained value 7,833 & gt; 3,07 , so the independent variable together influential dependent on variables .The results of the coefficients determination ( r ^ 2 ) obtained r square ( r ^ 2 ) as much as 0,160 it means variable work environment non-physical and compensation can explain variable of employee performance by 16 % and the rest 84 % can be explained by other variables that there is no in model .